Vermal cerebellar hemorrhage as the initial manifestation of undiagnosed hypertension - Iyagba, Alagoma; Onwuchekwa, Arthur (International Journal of Research in Medical Sciences, 2016)
Vermal cerebellar haemorrhage is bleeding affecting the midline region of the cerebellum. It is uncommon, accounting for 5-13% of all intracerebral haemorrhages. It is a grave condition with a high mortality. The diagnosis must be made early, if not, most patients would die within 48 hours. A 70-year-old lady presented to the accident and emergency department with a six hours history of sudden onset generalized tonic-clonic seizures following activity and loss of consciousness. She was unconscious with a Glasgow coma score of 3/15 with neck stiffness, generalized hypotonia and globally diminished reflexes. Her blood pressure was 240/120 mmHg with a mean arterial pressure of 160 mmHg. The brain computerized tomographic scan showed a hyperdense area in the cerebellar vermis with extension to both hemispheres and fourth ventricle. Consciousness was regained after three weeks of conservative management following which she became extremely restless and noticed to have developed titubations with nystagmus of both eyes. She also developed intention tremors, scanning dysarthria, generalized hypotonia, dysmetria, dysdiadochokinesia and intentional bilateral tremors. Her recovery was slow and gradual. Once she was able to stand with support, she was noticed to have florid truncal ataxia, lower limbs ataxia, and titubations.